A case report and literature review of immune checkpoint inhibitor-associated pneumonia caused by penpulimab - Gao, Rongmao; Yang, Fuxun; Yang, Chen; Zhang, Zhao; Liu, Mingzong; Xiang, Chunlin; Hu, Huan; Luo, Xiaoxiu; Li, Jiajia; Liu, Rongan (Frontiers in Immunology, 2023)
Immune checkpoint inhibitor-associated pneumonia (checkpoint inhibitor pneumonitis, CIP)[1] is a rare immune-related pulmonary adverse event caused by an immune checkpoint inhibitor (ICI), with a mortality rate of 17.5% according to the World Health Organization's drug alert database[2]. Because the disease’s clinical and pulmonary imaging manifestations are atypical, it can easily be confused with other conditions such as cytokine release syndrome, tumor, and infection; thus, clinical treatment becomes challenging and the disease often has disastrous consequences for patients, especially critical patients. Herein, we reviewed the successful treatment of a patient with lung squamous cell carcinoma complicated with lymphoma who recovered rapidly from severe CIP caused by penpulimab, an ICI. Notably, the patient's CIP diagnosis was not made by a chemist but by intensive care physicians. From the perspective of intensive care physicians, this paper reviews patient diagnosis and treatment approaches, analyzes and refines the relevant literature on CIP, and summarizes the characteristics of diagnosis and treatment of severe CIP to provide a basis and reference for the early identification, diagnosis, and treatment of patients with severe CIP.